Digitalisation and Bank Efficiency: Evidence from An Emerging Market - Le, Tu; Ngo, Thanh; Ho, Tin H; Do, Thuong TM (Asian Academy of Management Journal of Accounting and Finance, 2025)
This study empirically assesses the impact of digitalisation on bank efficiency in Vietnam using the two-stage framework for an unabalanced sample of 27 banks from 2010 to 2019. In the first stage, we use the conventional data envelopment analysis (DEA) to estimate bank efficiency scores. Then, these efficiency scores are regressed on environmental variables to determine factors affecting bank efficiency. The findings show a negative relationship between digitalisation and bank efficiency. However, the results indicate a U-shaped relationship between digitalisation and bank efficiency, being first impeded and then facilitated. Foreign-owned and state-owned banks are more efficient than their domestic and privately owned peers. Our results, however, show that the impact of digitalisation on bank efficiency does not vary among bank ownership and listing status. Furthermore, bank efficiency is negatively affected by bank size. The results further demonstrate that large banks with higher levels of digitalisation may not be beneficial, at least in the short run. Nonetheless, our study provides additional evidence to the extant literature on the association between digitalisation and bank efficiency. Our empirical evidence also offers motivations for banks to pursue ongoing digitalisation strategies when the banking system environment is more intensively competitive.